Essays in spatial economics and inequality - Heath Milsom, L (2023)
This thesis examines inequality both over space and in labor markets. The first chapter finds that birth location strongly affects educational outcomes in Benin Cameroon, and Mali --- opportunity is unevenly distributed over space. Place matters more for girls than boys, and local characteristics such as urbanization, access to electricity, and agricultural employment play a key role. Religion is also found to be correlated with gender differences in the effect of place on educational attainment. The second chapter uses historical road maps, a novel identification strategy, and a quantitative spatial economics framework, to show how road building alters the spatial distribution of opportunity. Some roads decrease inequality while others increase it. The chapter also highlights the equity-efficiency trade-off that policymakers face when choosing which roads to upgrade. Finally, the third chapter explores the role of occupations in explaining wage inequality using a two-way fixed effect model on UK administrative data. It finds that between-occupation heterogeneity accounts for a substantial proportion of log-wage variance, particularly in higher-wage occupations and larger labor markets. Overall, this thesis sheds light on the complex and interconnected factors shaping spatial inequality and suggests policy implications for promoting equitable access to opportunity.